Results of a non-interventional observational multicenter study of the management of patients with axial psoriatic arthritis in real-life clinical practice (NiSaXPA) - T. V. Korotaeva; E. E. Gubar; E. Yu. Loginova; Y. L. Korsakova; E. A. Vasilenko; I.-D. Yu. Ilyevsky; L. V. Ivanova; E. Yu. Akulinushkina; P. A. Shesternya; O. V. Matveychuk; Yu. Yu. Grabovetskaya; A. A. Barakat; et al. (Современная ревматология)
Psoriatic arthritis (PsA) is a chronic immunoinflammatory disease of the joints, spine and entheses from the group of spondyloarthritis, which is usually observed in patients with psoriasis. In recent years, the axial form of PsA (axPsA) has been actively researched. However, there is insufficient data on approaches to the diagnosis and treatment of patients with axPsA in real-life clinical practice. This article presents the results of an interim analysis of data from a non-interventional multicenter observational study on the treatment of patients with axPsA in real-life clinical practice (NiSaXPA) in Russian centers.Objective: to identify patients with axPsA, their characteristics and describe treatment tactics in real-life clinical practice.Material and methods. Patients with PsA who met the inclusion criteria were prospectively followed up during routine visits to a rheumatologist. Participants' axial radiographs were uploaded to a database in order for it to be confirmed the presence or absence of axPsA by two independent experts, a rheumatologist and a radiologist. Patients with a confirmed axPsA diagnosis participated in a further data collection phase (Visit 2, week 24).Results and discussion. Six hundred patients were enrolled into the study. At the time of analysis, 386 (64.3%) of them (209 men and 177 women) were screened for axPsA. The diagnosis of axPsA was confirmed in 241 (62.4%) cases; these patients formed the Per Protocol (PP) population. The mean age of patients with axPsA in the PP population was 46.30±12.6 years and the body mass index (BMI) was 27.4±5.2 kg/m2 . In 14.9% of patients, the duration of psoriasis was less than 1–5 years, in 21.5% – 5–10 years and in 63.6% – more than 10 years. The duration of PsA symptoms was less than 1–5 years in 31.2 % of patients, 5–10 years in 31.6 % and more than 10 years in 37.2 %. Low disease activity (BASDAI ˂ 4) was achieved in 33.3 % of patients with axPsA at visit 1 and in 64.3 % at visit 2; the BASDAI index declined on average from 4.67±1.95 to 3.31±1.89 points.In real-life clinical practice, patients were most frequently prescribed non-steroidal anti-inflammatory drugs (NSAIDs) – 88.7% and 71.7% (visits 1 and 2, respectively), and synthetic disease-modifying antirheumatic drugs (sDMARDs) –79.1% and 70.7%, respectively; therapy with biologic disease-modifying antirheumatic drugs (bDMARDs) was initiated in 40.2% and 60.6% of patients, respectively.Conclusion. The results of the interim analysis of this observational study showed that in 87.2% of patients who met the CASPAR criteria for PsA there was a suspicion of axial manifestations of PsA on the primary care level. However, only 62.4% of them had a confirmed diagnosis of axPsA on centralized expert assessment, which may indicate a possible overdiagnosis of axial lesions in real-life practice and emphasizes the importance of collaboration between a rheumatologist and a radiologist when analyzing the results of imaging studies. 33.3% of patients with axPsA had low disease activity according to BASDAI at baseline and 64.3% after 24 weeks, meaning that the disease was only adequately controlled in one third of cases despite therapy; the number of these patients doubled after a change in therapy. In real-world clinical practice, patients with axPsA are most commonly prescribed drugs from the NSAID and sDMARD groups; the frequency of use of biologic drugs varied between 40.2 and 60.6% by the end of the observation period.